The early reception of the Torah - De Troyer, Kristin; Schmitz, Barbara; Alfaro, Joshua; Häberlein, Maximilian 19XX- (Deuterocanonical and cognate literature studies, 2020)
This volume contains the papers presented at the 2017 meeting of the SBL Program Unit on Deuterocanonical and Cognate Literature in Boston, MA. The theme of the sessions was the interpretation of Torah in deuterocanonical literature. The contributions cover a variety of concepts and themes related to Torah and trace these through the Hebrew Bible, into the Septuagintal deuterocanonical books and other relevant and cognate literature.